The Aktualisasi Nilai-nilai Islam Nusantara terhadap Penguatan Moderasi Beragama di Indonesia - Aziz Fakhurokhman; Riyan Adyaputra; Muhammad Naufal Rachman; M. Ilham Ridho Mansyz; Brian Mayrezal Efandi; Muhamad Basyrul Muvid (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2022)
The purpose of this study is to analyze the concept of Islam Nusantara and the application of the values ​​in it to stem extreme ideas. Islam Nusantara is Islam that accepts differences, be it religion, ethnicity, race, or culture, so tolerance is needed to understand all the differences that exist, as well as in the moderation of religion in Indonesia, which has a strong background. The concept of religion is very appropriate to be applied in the life of the nation and state, especially in a multicultural society. To that end, Islam Nusantara established the concept of religious moderation as a mediation to resolve differences between radical and fundamentalist groups. The practice of religious moderation in a multicultural society makes educational institutions the basis of a laboratory for religious moderation and the application of socio-religious approaches in religion and the state.